An empirical analysis of hunter response to chronic wasting disease in Alberta. Issue 6 (1st November 2020) - Pattison-Williams, John K.; Xie, Lusi; Adamowicz, W. L. (Vic); Pybus, Margo; Hubbs, Anne
ABSTRACT: Chronic wasting disease (CWD) has impacted wildlife management in Canada. An integral partner in CWD management is the hunting community. This article empirically explored the response of Alberta mule deer hunters to CWD by modeling license application trends in areas where CWD has been positively detected in wild cervids. The relationship between resident draw applications and covariates of CWD prevalence, hunting quotas, draw success rates, licenses, and environmental indicators was examined with a fixed effects (FE) regression model. Results indicated that hunters are continuing to apply to hunt mule deer in areas with CWD and this relationship is not statistically impacted by the increasing prevalence of CWD. This outcome may be because CWD prevalence in Alberta is relatively low (but increasing), which is consistent with the literature indicating that few hunters avoid CWD zones until prevalence increases dramatically. Results also suggest that hunter-based strategies remain effective options for management.